2010
DOI: 10.1016/j.exger.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of endonuclease G in senescence-associated cell death of human endothelial cells

Abstract: Mitotic cells in culture show a limited replicative potential and after extended subculturing undergo a terminal growth arrest termed cellular senescence. When cells reach the senescent phenotype, this is accompanied by a significant change in the cellular phenotype and massive changes in gene expression, including the upregulation of secreted factors. In human fibroblasts, senescent cells also acquire resistance to apoptosis. In contrary, in human endothelial cells, both replicative and stress-induced prematu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…In addition, multiple CMP-induced genomic changes were linked to protracted stress, energy and calcium regulation as well as neurodegenerative processes, e.g. DNM1L [65], [66], SPTLC1 [67], [68]) and ENDOG [69]. Relatively novel CMP-controlled factors linked to neurodegeneration were uncovered, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiple CMP-induced genomic changes were linked to protracted stress, energy and calcium regulation as well as neurodegenerative processes, e.g. DNM1L [65], [66], SPTLC1 [67], [68]) and ENDOG [69]. Relatively novel CMP-controlled factors linked to neurodegeneration were uncovered, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This affects mitochondrial membrane integrity and triggers cytochrome c release35 to cause the activation of caspase‐9 and subsequently leads to the activation of effector caspase‐336 for causing apoptosis. In some cases, the mitochondrial dysfunction of cells will release apoptosis‐inducing factor (AIF)37 and endonuclease G (Endo G)38 to induce apoptosis directly.…”
mentioning
confidence: 99%
“…To the best of our knowledge, this is the first report that suggests the causative role of EndoG in mitotic endothelial cell death induced by cLDL or any other modified LDL. Interestingly, Diener and coauthors (17) recently suggested that under normal physiological conditions, EndoG protects endothelial cells from apoptosis and, at the same time, potentiates necrosis. This contradiction with our results can be perhaps explained by the difference in the cell death mechanisms between normal conditions and conditions resulting from cLDL toxicity.…”
Section: Discussionmentioning
confidence: 97%